Focus of Pi controllers on direct vector control of Induction Motors - Soto Lock, Alberto (2002)
Since it's invention, the Field Orientation Vector Control has been usefully for controlling Induction Machines (IM) for high dynamic performance. Among Field Orientation Vector Control methods. one uses leakage rotor referential flux, in order to reduce non linear model equations of IM to a system based on dq axes model, similar to DC motor. On this article, it is show fundamentals of this Vector Control method as well as a method for calibrating Proportional Integral controllers in order to archive a high dynamic performance IM control.